Desenvolvimento de um aditivo biodegradante e sua aplicação em nanocompósito de PEBD biodegradável e compostável - Menezez, Gabriela Messias Miranda (2022)
Due to the plastics accumulation in the environment, the search for strategies to confer biodegradability to these materials has grown, such as the insertion of biomolecules in polymeric materials during thermomechanical processing. In this context, the objective of this work was to develop a biodegradable additive to be applied as a promoter and facilitator of the biodegradation process of commercial low-density polyethylene (LDPE) in natural environments, such as soil. The biodegradable additive produced was characterized by spectroscopic and microscopic techniques, thermogravimetric analysis and measurement of enzymatic activity. After that, nanocomposites were produced by incorporating it into LDPE and the films of these materials (PE/additive) were characterized in terms of structural characteristics, morphology, thermal properties, behavior against the accelerated aging process and biodeterioration under composting conditions, as well as biodegradability in soil at 30°C for 83 days and isolation of possible biodegrading microorganisms present during this process. Finally, the ecotoxicity of the films without any previous treatment was evaluated by quantifying the dry and fresh mass and the length of the roots and shoots of the plant species Cucumis sativus L after 45 days. From the results obtained, the presence of the additive in the LDPE nanocomposite films was verified, which did not generate changes in the thermal properties of the polymer. The accelerated aging process led to many changes in the surface of pure PE and PE/additive, such as the appearance of micro cracks, as well as material fragmentation at the bulk level. Functional groups (C=O and –OH) were incorporated into the surface, modifying the structural characteristics of the samples. Changes in thermal properties were also observed after accelerated aging, such as a reduction in the initial temperatures of thermal degradation. Regarding the biodeterioration of the films before and after aging, the presence of a greater amount of adhered microorganisms was observed on the surface of the aged materials compared to the non-aged films. During the period of incubation of PE/additive in soil, a great production of CO2 was observed related to pure PE and similar behavior to the positive control of the assay. From the cultivation of these biodegraded films, ten strains of Gram-positive bacteria of bacillary morphology and two strains of filamentous fungi were isolated. Of the ten bacterial isolates, six were identified as belonging to the genera Bacillus and Lysinibacillus. PE/additive and pure PE films generated low toxicity to the growth and health of the evaluated plant species. Therefore, based on the results obtained, this work contributed to the understanding of the biodegradation and abiotic degradation process of a nanocomposite film of LDPE/biodegradable additive, as well as to the confirmation of the effectiveness of the developed additive, which is based on compounds and natural substances.